2011
DOI: 10.1038/modpathol.2010.189
|View full text |Cite
|
Sign up to set email alerts
|

P-cadherin expression as a prognostic biomarker in a 3992 case tissue microarray series of breast cancer

Abstract: P-cadherin is a calcium-dependent cell-cell adhesion glycoprotein. P-cadherin expression is restricted to the myoepithelial cells in normal breast tissue, and aberrant staining has also been described in invasive tumors. Several small studies have reported P-cadherin as a marker of poor outcome in breast cancer patients but its prognostic significance in relation to other variables has not been established in a large series of breast cancers. A tissue microarray was constructed from 3992 cases of invasive brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 84 publications
9
50
0
Order By: Relevance
“…MRM is decreasing and have been a non-mainstream operation pattern in developed countries (Ko et al, 2012;Piscitelli et al, 2012). While, our study showed MRM was still the major surgical treatment accounting for 71.8%, similar to another study from China (79.7%), which is much higher than developed counties/areas (Ko et al, 2012;Turashvili et al, 2011;Wei et al, 2010). As a safe treatment procedure, BCS has been expanded for more than 20 years since the National Institutes of Health Consensus Development Conference Statement was released advising breast conservation (Abrams et al, 1995).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…MRM is decreasing and have been a non-mainstream operation pattern in developed countries (Ko et al, 2012;Piscitelli et al, 2012). While, our study showed MRM was still the major surgical treatment accounting for 71.8%, similar to another study from China (79.7%), which is much higher than developed counties/areas (Ko et al, 2012;Turashvili et al, 2011;Wei et al, 2010). As a safe treatment procedure, BCS has been expanded for more than 20 years since the National Institutes of Health Consensus Development Conference Statement was released advising breast conservation (Abrams et al, 1995).…”
Section: Discussionsupporting
confidence: 64%
“…One notable fact is the relatively younger age of BC for Chinese females. The median age was 50 years in this study, which was similar to Shanghai (50 years) (Fan et al, 2009), Korean (49 years) (Ko et al, 2012), lower than Western developed countries (the United States: 62 years (Anderson et al, 2006); Canada: 60 years (Turashvili et al, 2011); German: 59 years (Fritz et al, 2010); Belgium: 58 years (Brouckaert et al, 2013) ). Percentage of BC < 50 years in America was 27.0% (Desantis et al, 2013), much lower than this study (47.0%).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…However, P-cadherin was described as being overexpressed in 20% to 40% of invasive breast carcinomas, as well as in 25% of ductal carcinomas in situ (DCIS) (Paredes et al, 2007a, Paredes et al, 2007b, Paredes et al, 2002. Most important, several studies have reported P-cadherin as a marker of poor prognosis in breast cancer, since P-cadherin-positive carcinomas were significantly associated with short-term overall and disease-specific survival, as well as with distant and loco-regional relapse-free interval (Gamallo et al, 2001, Peralta Soler et al, 1999, Turashvili et al, 2011. P-cadherin expression has also been positively associated with high histological grade tumours, as well as with well-established markers of poor prognosis, like Ki-67, epidermal growth factor receptor (EGFR), cytokeratin 5 (CK5), vimentin, p53, and HER2 expression and negatively associated with age at diagnosis, hormonal receptors (ER and PgR), and Bcl-2 expression.…”
Section: Prognostic Relevance Of P-cadherin In Breast Cancermentioning
confidence: 99%
“…Other MEC markers, such as SMA, p-cadherin, Wilms tumor 1 (WT1), S100, and high-molecular-weight cytokeratin (HMWCK) or basal-type cytokeratin (CK) (CK5/6, CK14, CK17, CK903) are less commonly used because of marked cross-reactivity with myofibroblasts and vascular SMA, [4][5][6][7][8][9]19,20 frequent reactivity in tumor cells (HMWCK or basal-type CK, S100, p-cadherin), [4][5][6][7][8]19,[32][33][34] or low sensitivity (WT1 and S100). 33 Podoplanin (D2-40), a marker labeling lymphatic endothelium, was observed to be variably expressed in breast MECs surrounding benign ducts and lobules as well as in CISs.…”
Section: The Evaluation Of Invasionmentioning
confidence: 99%